Culinary mapping and tourism development in South Africa’s Karoo region. - GE du Rand; Ingrid Booysen; Doreen Atkinson (African Journal of Hospitality, Tourism and Leisure, 2016)
Successful development of cuisine as a niche tourism product has been portrayed in various countries in the world. The paper argues that the Karoo provides evidence of a substantial culinary resource base and an established local food identity. This, in turn, can be promoted as a tourism destination by means of culinary mapping. Geographic Information Systems (GIS) tools are used, supported by a culinary database with information compiled from various sources in literature, the internet, lifestyle magazines, recipe books, census data and tourism structures. A proposed culinary route/itinerary synthesizes the data, identifying authentic food experiences as a niche tourism product, based on a regional cuisine.